Assessment Of Vertical Bone Loss Sites In Diabetic Patients With Chronic Periodontitis - A Retrospective Study - APARNA.M; GANESH.S, BALAJI; RAKSHAGAN V (The journal of contemporary issues in business and government, 2020)
Periodontitis is known as the sixth complication of diabetes mellitus. Alveolar bone loss is one of the major outcomes of periodontitis and diabetes is considered to be the primary risk factors for periodontal disease. Patients with diabetes mellitus have a greater chance of developing destructive periodontal disease as well as greater chance of experiencing progressive alveolar bone loss. The aim of this study is to assess the vertical bone loss sites among diabetic patients with chronic periodontitis. In this study sample size is selected according to inclusion criteria, among patients with both periodontitis and diabetes. Among 10,000 case records evaluated, a total of two hundred diabetic patients had periodontitis who were taken into the study. Vertical bone loss among each patient was assessed from the data retrieved from the dental records of Saveetha Dental College, Chennai. Overall, vertical bone loss was more common in maxillary posteriors than other teeth among diabetic patients with chronic periodontitis. It was commonly seen among males and was profoundly found in the age group of 30 to 50 years. The association between age and gender distribution with vertical bone loss sites was found to be statistically significant.